Micro/nano plastics in the urinary system: Pathways, mechanisms, and health risks - Huang, Hang; Lei, Pengyu; Yu, Haiyang; Du, Jiao; Wu, Baihui; Wang, Hanbing; Yang, Qinsi; Cheng, Yongwei; Sun, Da; Wan, Lijun (Environment international, 2024)
MNPs in the environment may enter the urinary system through blood circulation and potentially cause damage via mechanisms such as oxidative stress, inflammation, apoptosis, autophagy, and the “intestine-kidney axis”. [Display omitted] •Identified and reviewed the pathways through which MNPs enter and accumulate in the urinary system;•Summarized findings on MNPs’ urinary system toxicity, including oxidative stress, inflammation, and damage;•Investigated the synergistic toxicity of MNPs with other environmental pollutants;•Identified research gaps and proposed future directions to understand MNPs’ urinary system toxicity. Micro/Nano plastics (MNPs) pollutants are widespread in the environment, raising significant concerns about their biosafety. Emerging studies indicate that the urinary system is a primary accumulation site for MNPs, leading to severe tissue and functional damage. This review aims to summarize recent research on the potential hazards that MNPs may pose to the urinary system, highlighting the mechanisms of toxicity and the current state of knowledge. Studies have shown that MNPs enter the human body through drinking water, the food chain, inhalation, and skin contact. They may penetrate the bloodstream via the digestive, respiratory, and skin systems, subsequently dispersing to various organs, including the urinary system. The potential accumulation of MNPs in the urinary system might induce cellular oxidative stress, inflammation, apoptosis, autophagy, the “intestine-kidney axis”, and other possible toxic mechanisms. These processes could disrupt kidney metabolic functions and promote tissue fibrosis, thereby potentially increasing the risk of urinary system diseases. Despite ongoing research, the understanding of MNPs’ impact on the urinary system remains limited. Therefore, this review provides a comprehensive overview of MNPs’ potential toxicity mechanisms in the urinary system, highlights key challenges, and outlines future research directions. It offers a theoretical basis for the development of effective protective measures and policies.